Low Levels of Low-Density Lipoprotein Cholesterol and Endothelial Function in Subjects without Lipid-Lowering Therapy - Takaeko, Yuji (J Clin Med, 2020)
An elevation of serum low-density lipoprotein cholesterol (LDL-C) levels has been associated with endothelial dysfunction in statin naïve subjects. However, there is no information on endothelial function in subjects with extremely low levels of LDL-C. The purpose of the present study was to determine the relationship of LDL-C levels, especially low levels of LDL-C, with endothelial function. Endothelial function assessed by flow-mediated vasodilation (FMD) measurement and LDL-C levels were evaluated in 7120 subjects without lipid-lowering therapy. We divided the subjects into five groups by LDL-C levels: <70 mg/dL, 70–99 mg/dL, 100–119 md/dL, 120–139 mg/dL, and ≥140 mg/dL. FMD values were significantly smaller in subjects with LDL-C levels of ≥140 mg/dL than in those with LDL-C levels of 70–99 mg/dL and 100–119 mg/dL (p < 0.001 and p = 0.004, respectively). The FMD values in the LDL-C of <70 mg/dL group were not significantly different from those in the other groups. To evaluate the relationship of extremely low LDL-C levels with endothelial function, we divided the subjects with LDL-C of <70 mg/dL into those with LDL-C levels of <50 mg/dL and 50–69 mg/dL. FMD values were similar in the LDL-C <50 mg/dL group and ≥50 mg/dL group in the propensity score-matched population (p = 0.570). A significant benefit was not found in subjects with low LDL-C levels from the aspect of endothelial function.